2005
DOI: 10.1584/jpestics.30.1
|View full text |Cite
|
Sign up to set email alerts
|

QSAR for Binding Affinity of Substituted Dibenzoylhydrazines to Intact Sf-9 Cells

Abstract: The binding affinity to intact Sf-9 cells was measured in a series of N-t-butyl-N,NЈ-dibenzoylhydrazine congeners. The benzene ring close to the t-butyl group of the compounds was substituted with Cl at the ortho-position and the other benzene ring was variously substituted at the para-position. The effects of the substituent on the binding affinity were analyzed quantitatively using the Hansch-Fujita QSAR method. The introduction of hydrophobic and electron-donating substituents at the para-position enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…Nakagawa's research [50] indicated hydrophobic, steric, and electrostatic effects were likely favorable to the larvicidal activity, which is consistent with our QSAR results. The accurate quantum chemical descriptors were used in our research, while the semiempirical parameters were used in Nakagawa's research.…”
Section: Qsar Analysis and Model Validationsupporting
confidence: 91%
See 2 more Smart Citations
“…Nakagawa's research [50] indicated hydrophobic, steric, and electrostatic effects were likely favorable to the larvicidal activity, which is consistent with our QSAR results. The accurate quantum chemical descriptors were used in our research, while the semiempirical parameters were used in Nakagawa's research.…”
Section: Qsar Analysis and Model Validationsupporting
confidence: 91%
“…(5)) showed that the electron-donating ability of the carbonyl group significantly affected the activity of the target compounds, where the larger the weighted electrophilic electron density of the oxygen atom marked with asterisk symbol, the higher the activity. Ogura et al [50] also reported the electron effects of the oxygen atom on the carbonyl group were significant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To determine the physicochemical mechanism of these substituents, binding activity was quantitatively analyzed using substituent parameters. We previously demonstrated that the hydrophobicity of substituent is important for the binding of DAHs to the ecdysone receptor of Sf-9 cells [33]. Therefore, activity was quantitatively analyzed using hydrophobicity ΔClogP [ClogP (X) -ClogP (H)] to formulate statistically significant values using Eq.…”
Section: Qsar Analysismentioning
confidence: 99%
“…Ogura and co-workers quantitatively analyzed the binding activity of 20 DBHs (X = 2−Cl) with various substituents (Y) at the para -position of B-ring as shown in Eq. 7.9 (Ogura et al 2005 ) . The electronic effect at the B-ring moiety on the larvicidal and molting hormonal activity was not signi fi cant, while an electron-donating group at the B-ring is favored for receptor binding.…”
Section: Substitution Atmentioning
confidence: 99%